(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article substantiates the theoretical and methodological foundations for the introduction of an activity-based approach to training competent engineers when studying a course of physics. Contemporary requirements of the agro-industrial complex require integration of the fundamental knowledge with practical skills, which makes this approach the key element of the educational process when studying a course of physics. There are considered the concepts and principles of teaching, aimed at the development of professional thinking, the ability to make decisions in non-standard situations and efficient work with digital technologies, when studying the course of physics. There are identified the pedagogical tools that promote the development of critical thinking, independence and continuous self-development of the students in the process of mastering physics. Methodological recommendations are provided for the creation of a productive educational environment, including interaction with agro-industrial enterprises and individualization of learning when studying the physics course. An analysis of the implementation of the activity-based approach showed its efficiency: the average score of the students in the experimental group increased by 15–20%, and the success rate of completing the practical assignments increased by 20–25% when studying the physics course. The project activities contributed to the development of systems thinking and an innovative approach to solving the production problems, which is especially important when mastering physics. A conclusion is made about the need to introduce an activity-based approach to train competitive specialists, adapted to the modern challenges of the agro-industrial complex, which, in turn, contributes to the formation of an innovative educational environment, focused on the development of professional competencies, engineering creativity and practical training of the students when studying the physics course.